2014
DOI: 10.4236/ojvm.2014.46013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effects of Velogenic Newcastle Disease Virus Infection on the Hematology of Ducks and Chickens

Abstract: The hematological lesions consequent upon velogenic Newcastle disease virus (NDV) infection were investigated in 6-week-old ducks and chickens. Following intramuscular inoculation, the results indicated significantly lower (p < 0.05) packed cell volume (PCV) in infected chickens (IC) on days 3 -9 post inoculation (PI) and in infected ducks (ID) on days 3 -15 PI. The hemoglobin concentrations were significantly lower (p < 0.05) in IC on days 3, 6 and 15 PI while in the ID, they were significantly lower (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
3
1
2
Order By: Relevance
“…Besides, in our study, the values of RBC in the mallard ducks within all monitored groups were slightly higher than those found by He et al (2013) in 35-day-old Cherry Valley hybrid ducks. On the other hand, the values of RBC that we found are somewhat lower than the values found by Eze et al (2014) in 21-day-old domestic mallard ducks. Concerning the values of the HCT, the values that we found corresponded to the values found by He et al (2013).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Besides, in our study, the values of RBC in the mallard ducks within all monitored groups were slightly higher than those found by He et al (2013) in 35-day-old Cherry Valley hybrid ducks. On the other hand, the values of RBC that we found are somewhat lower than the values found by Eze et al (2014) in 21-day-old domestic mallard ducks. Concerning the values of the HCT, the values that we found corresponded to the values found by He et al (2013).…”
Section: Discussioncontrasting
confidence: 98%
“…Such a comparison can affect negatively Boever et al 2010;Seliger et al 2012;Bílková et al 2017). Besides, our results of the differential leukocyte counts in Cherry Valley hybrid ducks showed that LYM are the most abundant type of leukocytes, which is in accordance with the previous findings of Li et al (2012) and Eze et al (2014). The LYM and GRA values found in our study are generally in accordance with those stated by Campbell et al (2010) for mallard ducks, while their percentage shares did not differ from the respective groups of ducks in our study (P > 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…Vaccination in pullets protected against ND and lesions of velogenic NDV in laying birds (Igwe and Eze, 2016). Only the values obtained in turkeys agreed with the reports of Eze et al (2014) who observed significant reductions in erythrocytic values from day 3 to 15 pi in unvaccinated and infected chickens and ducks. It is possible that a less virulent strain of the virus was used by Eze et al (2014) as several birds survived at the end of the experiment unlike what was observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of significantly lower RBC on day 6 PI and all the erythrocytic parameters (PCV, RBC and HbC) on day 15 PI in unvaccinated infected laying chickens are similar to the findings of Hostetter & Andreasen (2004). Although, different pattern of reduced erythrocytic parameters beginning from day 3 PI was reported by Abbas et al (1992) and Eze et al (2014) in 6-week old pullets and cockerels respectively, experimentally infected with vNDV, the pattern observed in the present study was in line with the report of Hostetter & Andreasen (2004).…”
Section: Discussionsupporting
confidence: 82%
“…The mean corpuscular values are useful in the characterization of the erythrocytes, especially in the evaluation of anaemia (Campbell, 1994). The significant higher MCV value recorded in the present study in UI laying chickens is in agreement with the findings of Eze et al (2014), while the higher MCH are contrary to their report. The finding of no significant changes in MCHC is in agreement with the report of Igwe et al (2013).…”
Section: Discussioncontrasting
confidence: 55%